Antibiotic Susceptibility Pattern of Bacteria Causing Urinary Tract Infection at Nepalgunj Medical College - Gurung, Kishor; KC, Rupak; Patel, Ishant; Neupane, Dhan Raj; Pokhrel, Sandeep; Gurung, Samjhana (Journal of Nepalgunj Medical College, 2022)
Introduction: Urinary Tract Infection is one of the most common infectious diseases affecting people of all age groups. Resistance to antibiotics is highly prevalent in bacterial isolates.Aims: This study was carried out to isolate the different microbial agents and evaluate their antibiograms pattern.Methods: Hospital based descriptive cross sectional study was conducted over the period of October 2021 to January 2022 at Nepalgunj Medical College, Kohalpur, Nepal. 292 urine samples were inoculated on cysteine lactose electrolyte deficient agar and incubated at 37 0C in incubator. After overnight growth, Gram positive and Gram negative bacteria were identified on the basis of different biochemical tests. Antibiotic sensitivity test was performed by Kirby-Bauer disk diffusion method.Results: Out of 292 urine samples, 28.76 % showed microbial growth. Majority of isolates were Escherichia coli and Staphylococcus aureus. Most vulnerable age group was 26-50 years. Overall pathogens were sensitive to amikacin, gentamicin, nitrofurantoin but resistant to cefixime.Conclusion: Regular surveillance of the resistance is required among microorganisms to ensure the appropriate therapy of Urinary tract infection.